Moving with the times: new developments in languages in French higher education contexts. Issue 2 (1st October 2020) - Whyte, Shona
Abstract : Since the turn of the century, the increasing internationalisation of French higher education has been felt in research and teaching across a broad range of disciplines. The challenges and opportunities affect different sectors of foreign language (FL) education, including modern foreign language (MFL) studies, languages for specific purposes (LSP) and FL certification. This paper offers a review of recent developments in these three areas in France and other European countries, before examining a key difference in French higher education (HE), that is, the schism between second language acquisition (SLA) and language didactics ( didactique des langues, DDL). A historical overview of developments in applied linguistics is followed by a panorama of the French language education research community today. The last section of the paper presents three new research networks taking an interdisciplinary perspective on SLA and FL education offering ways to bring together different interests within an expanded understanding of applied linguistics and opening up promising avenues for future collaboration.